Case Study of Blowing Snow Impacts on the Antarctic Peninsula Lower Atmosphere and Surface Simulated With a Snow/Ice Enhanced WRF Model - Luo, Liping; Zhang, Jing; Hock, Regine; Yao, Yao (Journal of Geophysical Research: Atmospheres, 2021)
To better capture the air-snow-ice interaction, a snow/ice enhanced Weather Research and Forecasting (WRF-ice) model has been developed. This study examines the performance of WRF-ice and its blowing snow component during a strong cyclone event from October 23 to 27, 2017 over the Antarctic Peninsula, which is characterized by a synoptic cyclone crossing the northern part of the Peninsula and an embodied mesoscale cyclone over the Weddell Sea. Evolution of the cyclone is accurately reproduced in the 5-km resolution WRF-ice simulation, and the simulated near-surface conditions agree well with station and satellite observations. Numerical simulations show that the process of blowing snow sublimation can be prominent within the lower atmosphere when the air is dry, and produces moistening and cooling effects. Over relatively warm and humid areas, cloud enhancement by blowing snow can lead to either colder or warmer surfaces because of competing effects of longwave and shortwave cloud radiative forcings. In particular, additional moisture from blowing snow sublimation can slightly intensify precipitation over the mountains. Surface energy budget analysis indicates that absorbed shortwave (Sa), incoming longwave (Ld), and outgoing longwave (Lu) are dominant components of surface energy budget. When increases in Ld, Lu, and sensible heat flux are combined with decreases in Sa and latent heat flux due to blowing snow effects, a negative surface net heat flux (∼0.5 W/m2) occurs during daytime. A positive domain-total surface mass balance (∼0.43 Gt) is generated during the simulated cyclone event due to increases in precipitation, decreases in runoff, and decreases in sublimation.
Keywords: Antarktis; akkumulasjon; atmosfæren; geofysikk; geovitenskap; is; meteorologi; polarområdene; satellite; snø

Linking Sub-Tropical Evaporation and Extreme Precipitation Over East Antarctica: An Atmospheric River Case Study - Terpstra, Annick; Gorodetskaya, Irina V; Sodemann, Harald (Journal of Geophysical Research: Atmospheres, 2021)
We investigate an intense snowfall event between 15 and 18 February 2011 over the East Antarctic coastal region which contributed to roughly 24% of the annual snow accumulation. The event was previously associated with an atmospheric river, and here we use both Eulerian and Lagrangian analysis to gain an understanding of the processes contributing to the atmospheric river signature. The planetary-scale configuration during the event consisted of a persistent blocking situation resulting in a sustained meridional flow from the sub-tropics to the Antarctic ice sheet between 20 and 50°E. Within this configuration, synoptic-scale cyclogenesis contributed to slantwise ascent of moisture loaded air parcels toward Antarctica. Landfall of this cyclone’s warm sector coincided with the onset of Antarctic precipitation. Subsequently, a secondary cyclone developed along a pre-existing baroclinic zone. The rapid intensification and propagation speed of this mesoscale cyclone alongside the warm, moist air mass resulted in strong moisture flux convergence ahead of the cyclone, providing additional poleward moisture transport. The poleward progression of warm moist air and a corresponding decrease of sea-surface temperatures implied downward surface sensible and latent heat fluxes throughout the region of intense poleward moisture, roughly between 40 and 60°S. Hence, moisture uptake via surface evaporation was suppressed between the sub-tropics and the polar continent, favoring long-range transport. Identification of the surface moisture uptake region by tracing changes in moisture in air parcels confirmed the limited uptake of moisture during the poleward transport in this case study, with the primary moisture source for Antarctic precipitation located in the sub-tropics.
Keywords: Antarktis; akkumulasjon; atmosfæren; geofysikk; meteorologi; nedbør; snøfall

Variability of Sediment Accumulation Rates in an Antarctic Fjord - Eidam, Emily F.; Nittrouer, Charles; Lundesgaard, Øyvind; Homolka, Khadijah; Smith, Craig (Geophysical Research Letters, 2019)
Fjords on the West Antarctic Peninsula (WAP) serve as sediment traps, preserving histories of glacial sediment supply. Regional warming trends are expected to change sediment supplies, altering water quality, depositional history, and ecosystem drivers. Our ability to assess magnitudes of these changes is limited by sparse data on modern sediment accumulation. Twelve new cores and four existing cores from Andvord Bay were used to characterize variability in sediment accumulation rates. These range from 1.5 to 7.9 mm/year (0.12 to 0.56 g·cm−2·year−1). Spatial differences and a weak down-fjord gradient in rates suggest diverse sediment sources, including from outside the fjord. This data set provides a comprehensive assessment of sedimentation during the past century, indicating little change in rates due to recent WAP warming, and sets a benchmark for assessing climate-related changes in sediment delivery and ecosystem drivers (e.g., burial disturbance) in the fjord over coming decades.
Keywords: Antarktis; akkumulasjon; bentiske organismer; biodiversitet; fjord; glasiologi; sedimenter; sedimentologi; tidevannsbreen

Variation of accumulation rates over the last eight centuries on the East Antarctic Plateau derived from volcanic signals in ice cores - Anschütz, Helgard; Sinisalo, Anna; Isaksson, Elisabeth; McConnell, Joseph R; Hamran, Svein Erik; Bisiaux, M M; Pasteris, Daniel R; Neumann, Thomas; Winther, Jan-Gunnar (Journal of Geophysical Research: Atmospheres, 2011)
Volcanic signatures in ice-core records provide an excellent means to date the cores and obtain information about accumulation rates. From several ice cores it is thus possible to extract a spatio-temporal accumulation pattern. We show records of electrical conductivity and sulfur from 13 firn cores from the Norwegian-USA scientific traverse during the International Polar Year 2007–2009 (IPY) through East Antarctica. Major volcanic eruptions are identified and used to assess century-scale accumulation changes. The largest changes seem to occur in the most recent decades with accumulation over the period 1963–2007/08 being up to 25% different from the long-term record. There is no clear overall trend, some sites show an increase in accumulation over the period 1963 to present while others show a decrease. Almost all of the sites above 3200 m above sea level (asl) suggest a decrease. These sites also show a significantly lower accumulation value than large-scale assessments both for the period 1963 to present and for the long-term mean at the respective drill sites. The spatial accumulation distribution is influenced mainly by elevation and distance to the ocean (continentality), as expected. Ground-penetrating radar data around the drill sites show a spatial variability within 10–20% over several tens of kilometers, indicating that our drill sites are well representative for the area around them. Our results are important for large-scale assessments of Antarctic mass balance and model validation.
Keywords: Antarktis; akkumulasjon; geovitenskap; glasiologi; innlandsis; iskjerner; klimatologi

Ground-based measurements of spatial and temporal variability of snow accumulation in East Antarctica - Eisen, Olaf; Frezzotti, Massimo; Genthon, Christophe; Isaksson, Elisabeth; Magand, Olivier; van den Broeke, Michiel R; Dixon, Daniel A; Ekaykin, Alexey; Holmlund, Per; Kameda, Takao; Karlöf, Lars; Kaspari, Susan; et al. (Reviews of Geophysics, 2008)
The East Antarctic Ice Sheet is the largest, highest, coldest, driest, and windiest ice sheet on Earth. Understanding of the surface mass balance (SMB) of Antarctica is necessary to determine the present state of the ice sheet, to make predictions of its potential contribution to sea level rise, and to determine its past history for paleoclimatic reconstructions. However, SMB values are poorly known because of logistic constraints in extreme polar environments, and they represent one of the biggest challenges of Antarctic science. Snow accumulation is the most important parameter for the SMB of ice sheets. SMB varies on a number of scales, from small-scale features (sastrugi) to ice-sheet-scale SMB patterns determined mainly by temperature, elevation, distance from the coast, and wind-driven processes. In situ measurements of SMB are performed at single points by stakes, ultrasonic sounders, snow pits, and firn and ice cores and laterally by continuous measurements using ground-penetrating radar. SMB for large regions can only be achieved practically by using remote sensing and/or numerical climate modeling. However, these techniques rely on ground truthing to improve the resolution and accuracy. The separation of spatial and temporal variations of SMB in transient regimes is necessary for accurate interpretation of ice core records. In this review we provide an overview of the various measurement techniques, related difficulties, and limitations of data interpretation; describe spatial characteristics of East Antarctic SMB and issues related to the spatial and temporal representativity of measurements; and provide recommendations on how to perform in situ measurements.
Keywords: Antarktis; akkumulasjon; fjernmåling; glasiologi; havnivåstigning; innlandsis; paleoklimatologi; snø

Spatial and temporal variations in the thermodynamics since the Last Glacial Maximum at Jutulstraumen drainage basin, East Antarctica - Rolstad, Cecilie (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 2006)
Publisher: Routledge
Keywords: Antarktis; akkumulasjon; glasiologi; isstrøm; nunataker

A century of accumulation and temperature changes in Dronning Maud Land, Antarctica - Isaksson, Elisabeth; Karlén, Wibjörn; Gundestrup, Niels; Mayewski, Paul; Whitlow, Sallie; Twickler, Mark (Journal of Geophysical Research: Atmospheres, 1996)
Keywords: Dronning Maud Land; akkumulasjon; klima; målinger; snø; temperatur

Snowdrifts around buildings and stores - Roots, Ernest Frederick; Swithinbank, Charles (Polar Record, 1955)
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; akkumulasjon; forskningsstasjoner; snø